Activity-Guided Isolation of Antioxidant Compounds from Rhizophora apiculata - Gao, Mingzhe (Molecules, 2012)
Rhizophora apiculata (R. apiculata) contains an abundance of biologically active compounds due its special salt-tolerant living surroundings. In this study, the total phenolic content and antioxidant activities of various extract and fractions of stem of R. apiculata were investigated. Results indicated that butanol fraction possesses the highest total phenolic content (181.84 mg/g GAE/g dry extract) with strongest antioxidant abilities. Following in vitro antioxidant activity-guided phytochemical separation procedures, lyoniresinol-3α-O-β-arabinopyranoside (1), lyoniresinol-3α-O-β-rhamnoside (2), and afzelechin-3-O-L-rhamno-pyranoside (3) were separated from the butanol fraction. These compounds showed more noticeable antioxidant activity than a BHT standard in the DPPH, ABTS and hydroxyl radical scavenging assays. HPLC analysis results showed that among different plant parts, the highest content of 1–3 was located in the bark (0.068%, 0.066% and 0.011%, respectively). The results imply that the R. apiculata might be a potential source of natural antioxidants and 1–3 are antioxidant ingredients in R. apiculata.